Istitratiyyah Al-Madrasah Al-Mustanida 'Ala Al-Ma'had Al-Islami Fi Tashkili Shakhsiyyati Ath-Thullab Wa Bina'i Akhlaqihim (Dirasah Haaliyah Fi Al-Madrasah Ats-Tsanawiyyah Al-Muhni'ah Syafi'i Akram Pekalongan Jawa Al-Wustha). - Udin Zaenudin (Jurnal Hikmatuna, 2016)
The vocational school program with an Islamic Boarding School-based approach is an initiative aimed at cultivating well-rounded and nationally-oriented young generations who possess intellectual, emotional, spiritual, and kinesthetic/vocational intelligences. This is achieved by integrating vocational education with the principles of Islamic boarding schools, with the goal of producing competent graduates who excel not only in science and technology but also in their faith, piety, and character. SMK Syafi'i Akrom focuses on developing the students' character, which is characterized by religiousness, independence, discipline, respect, and peacefulness. The school employs several strategies to nurture these qualities: 1. Establishing clear school policies that promote character development.2. Fostering a strong commitment to character education among the school principal and the entire school community.3. Implementing effective strategies to cultivate students' character. By adopting these strategies, SMK Syafi'i Akrom aims to ensure the holistic development of their students, equipping them with not only vocational skills but also with strong moral values and virtuous character traits.